2018
DOI: 10.3390/ijms19030777
|View full text |Cite
|
Sign up to set email alerts
|

Expression of Phospho-ELK1 and Its Prognostic Significance in Urothelial Carcinoma of the Upper Urinary Tract

Abstract: Using preclinical models, we have recently found that ELK1, a transcriptional factor that activates downstream targets, including c-fos proto-oncogene, induces bladder cancer outgrowth. Here, we immunohistochemically determined the expression status of phospho-ELK1, an activated form of ELK1, in upper urinary tract urothelial carcinoma (UUTUC). Overall, phospho-ELK1 was positive in 47 (47.5%; 37 weak (1+) and 10 moderate (2+)) of 99 UUTUCs, which was significantly (P = 0.002) higher than in benign urothelium (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 24 publications
1
8
0
Order By: Relevance
“…ELK1 functions through phosphorylation and can be regulated by the mitogen‐activated protein kinase (MAPK) pathway 10,11 . Interestingly, ELK1 is highly expressed and hyperactivated in some cancers, including gastric cancer, 12 urothelial carcinoma, 13 hepatocarcinoma, 14 and cervical and endometrial carcinomas 15 . A global analysis of TFs suggested that ELK1 is an important TF, involved in CRC progression, and might be a potential biomarker for CRC treatment 16 .…”
Section: Introductionmentioning
confidence: 99%
“…ELK1 functions through phosphorylation and can be regulated by the mitogen‐activated protein kinase (MAPK) pathway 10,11 . Interestingly, ELK1 is highly expressed and hyperactivated in some cancers, including gastric cancer, 12 urothelial carcinoma, 13 hepatocarcinoma, 14 and cervical and endometrial carcinomas 15 . A global analysis of TFs suggested that ELK1 is an important TF, involved in CRC progression, and might be a potential biomarker for CRC treatment 16 .…”
Section: Introductionmentioning
confidence: 99%
“…We demonstrated, using SVHUC cells with carcinogen challenge, that knockdown of ELK1 or treatment with a selective α 1 -blocker silodosin, which could inactivate ELK1, prevented the MCA-induced neoplastic formation of SVHUC-AR cells [35], indicating the oncogenic role of ELK1 in urothelial cancer. Our immunohistochemical studies in bladder [76] and UUT [77] specimens showed significant up-regulation of the expression of ELK1 and/or its activated form phospho-ELK1 in tumors, compared with non-neoplastic urothelial tissues. In addition, phospho-ELK1 positivity in non-muscle-invasive bladder tumors was associated with a significantly higher risk of disease recurrence [76].…”
Section: Elk1mentioning
confidence: 59%
“…Using the identical UUTUC TMA, we previously determined the expression status of various transcription factors (20,(23)(24)(25)(26). Notably, the positive rates of 6 transcription factors, including AR (20), ERβ (20), GATA-binding protein 3 (GATA3) (23), zinc finger with KRAB and SCAN domains 3 (ZKSCAN3) (24), nuclear factor of activated T-cells 1 (NFATc1) (25) and a phosphorylated form of ELK1 (p-ELK1) (26), were significantly (P<0.05; GATA3, ZKSCAN3) or insignificantly (0.05≤P<0.1; AR, ERβ, NFATc1, p-ELK1) different between renal pelvic and ureteral tumor samples, although the underlying reasons remain unclear.…”
Section: Discussionmentioning
confidence: 99%